PENERIMAAN E-MONEY: PENERAPAN UNIFIED THEORY OF ACCEPTANCE AND USE OF TECHNOLOGY (UTAUT) MODEL - Christiana, Irma; Febriaty, Hastina; Putri, Linzzy Pratami (Universitas Muhammadiyah Palembang, 2024)
ABSTRACT Purpose– This research aims to identify any variables that can influence e-money user behavior mediated by behavioral intentions using the UTAUT model Design/methodology–. This research uses a quantitative-descriptive approach. Sampling used a purposive sampling method to achieve a sample size based on the Slovin formula. Data was collected by distributing a questionnaire in the form of a Google Form. The data analysis technique uses the Partial Least Squares-Structural Equation Model (PLSSEM) with the SmartPLS3 application.Findings - The results of hypothesis testing show that performance expectations do not influence behavioral intentions. Effort expectancy, social influence, and facilitating conditions influence the intention to use e-money. Facilitating conditions influence user behavior. Behavioral intentions are able to mediate the influence of performance expectations, business expectations, and social influences, as well as facilitate conditions on e-money user behavior.